2021
DOI: 10.52312/jdrs.2021.51
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of a new intercalary modular endoprosthesis for the management of diaphyseal bone metastases

Abstract: Objectives: This study aims to evaluate functional outcomes of patients and to analyze complication rates of modular intercalary endoprosthetic reconstruction after resection of metastatic diaphyseal bone lesions. Patients and methods: Between December 2017 and February 2020, 22 patients (15 males, 7 females; median age: 64.2 years; range, 49 to 91) who underwent reconstruction with modular intercalary endoprostheses for metastatic bone tumors at five different centers were retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Similarly, Pu et al [15] and Huang et al [13] reported total MSTS scores of 84.6% and 95.3% at the final follow-up interval in patients with humeral and femoral diaphyseal metastatic lesions, respectively. Another study that included tibial implants noted early short-term gains in functional outcome scores [5]. Our patients with femoral implants consistently returned early to ambulation, and most patients did not rely on any external support.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Similarly, Pu et al [15] and Huang et al [13] reported total MSTS scores of 84.6% and 95.3% at the final follow-up interval in patients with humeral and femoral diaphyseal metastatic lesions, respectively. Another study that included tibial implants noted early short-term gains in functional outcome scores [5]. Our patients with femoral implants consistently returned early to ambulation, and most patients did not rely on any external support.…”
Section: Discussionmentioning
confidence: 57%
“…However, prior studies have emphasized the treatment of primary sarcomas, and there is little research examining outcomes specifically in the setting of metastatic lesions [8,13,15,17,18]. In one recent study of 22 patients with metastases, short-term improvements were noted in pain and functional outcome, but six of the 22 patients had implant failures of different modes including aseptic loosening, breakage, and infection [5]. Furthermore, there have not been attempts in the past at estimating the cumulative risk of implant revision or aseptic loosening while considering death as a competing risk for patients with metastatic disease and limited overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis also revealed that the highest deformation recorded was 1.3871e-008 m, Fig (16). In the tensile test, the maximum stress seen was recorded as 6.6012e+006 Pa, Fig (17), while the corresponding largest deformation was measured at 1.0458e-006 m, Fig (18). All the numerical results of the tests were summarized in Table 2.…”
Section: Resultsmentioning
confidence: 75%